Treatment of chondral lesions in advanced osteochondritis dissecans: A comparative study of the efficacy of chondrocytes, mesenchymal stem cells, periosteal graft, and mosaicplasty (osteochondral autograft) in animal models - Hui, J.H.P. (2013)
Journal of Pediatric Orthopaedics